A Case Report of Hennessey-Induced Urticaria in a Healthcare Centre in Suburban Africa - Ashinze, Patrick; Ajao, Mayowa Kabir (Scripta Medica, 2024)
This case report explores the unprecedented manifestation of generalised urticaria consistently affecting specific body surfaces in a 25-year-old female patient following Hennessy consumption. The patient’s medical history aligns with existing literature implicating alcohol as a potential trigger for urticarial symptoms. While the pathogenesis of mast cell activation due to alcohol remains elusive, presented findings contribute to the growing body of knowledge. The case underscores the importance of recognising alcohol as a potential aetiological factor for urticaria. This unique presentation of generalised urticaria prompts clinicians to consider alcohol-induced urticaria in their differential diagnosis. This case report contributes to the evolving understanding of urticaria pathogenesis, urging continued exploration into the complex relationship between alcohol consumption and urticarial pathogenesis.